2020
DOI: 10.3389/fneur.2020.00844
|View full text |Cite
|
Sign up to set email alerts
|

The Proteome and Secretome of Cortical Brain Cells Infected With Herpes Simplex Virus

Abstract: Infections of the brain with herpes simplex virus type 1 (HSV-1) cause life-threatening Herpes simplex encephalitis (HSE) characterized by viral replication in neurons and neuro-inflammation including an infiltration of peripheral immune cells. HSV-1 reprograms host cells to foster its own replication and for immune evasion, but eventually the immune responses clear the infection in most patients. However, many survivors suffer from long-term neuronal damage and cannot regenerate all brain functions. HSV-1 inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 70 publications
(96 reference statements)
0
5
0
Order By: Relevance
“…215,216 Through their activation via CD36, CD14, CD47 and TLRs (especially TLR4), microglia produce pro-inflammatory cytokines and chemokines. [217][218][219] The role of microglia is well established in various cerebral infections 220,221 however, there are no data related to the infection hypothesis of AD at the exception of one study that reported the relation between microglia and some changes of microbiota and its derivatives including LPS, as well as related to the genetic background such as ApoE4. 222 Therefore, it would be interesting to assess how microglia could behave at different stages of AD.…”
Section: Cellular Defensementioning
confidence: 99%
“…215,216 Through their activation via CD36, CD14, CD47 and TLRs (especially TLR4), microglia produce pro-inflammatory cytokines and chemokines. [217][218][219] The role of microglia is well established in various cerebral infections 220,221 however, there are no data related to the infection hypothesis of AD at the exception of one study that reported the relation between microglia and some changes of microbiota and its derivatives including LPS, as well as related to the genetic background such as ApoE4. 222 Therefore, it would be interesting to assess how microglia could behave at different stages of AD.…”
Section: Cellular Defensementioning
confidence: 99%
“…Succinctly, HSV-1 infection in the brain not only instantly affects the physiology of neurons, astrocytes, microglia, and oligodendrocytes, significantly altering their protein levels and morphology [ 265 ], but also leads to heavy cell damage and death. Interestingly, the virus exploits molecular strategies to evade host cell death through suppression of both host cell death pathways for the benefit of viral replication [ 228 ]; yet, the entry and spread of HSV-1 in the CNS leads to severe and long-term brain damage.…”
Section: Neuronal and Glial Cell Injury And Loss Combined With Advanced Agementioning
confidence: 99%
“…By comparing temporal proteome changes during WT and d106 HSV-1 infections, we discovered the upregulation of several proteins involved in innate immunity and apoptosis, and integration with cGAS IP-MS led to the discovery of OASL-mediated cGAS inhibition [51]. Additional MS studies have been carried out to characterize proteome changes during HSV-1 infection in a range of cell types and to compare alterations induced by different virus strains [51,54,104,[111][112][113][114][115][116][117][118][119][120][121]. Spatial proteomics [122] has further provided the ability to characterize changes in proteome organization during infection [123], as well as discover viral proteins that localize to distinct organelles to regulate their functions, as shown for HCMV infection [124].…”
Section: Defining the Cellular Landscape Representative Of Immune Activationmentioning
confidence: 99%
“…For example, quantitative proteomic analysis of exosomes from HSV-1-infected macrophages demonstrated that specific subsets of cytokines, inflammatory proteins, and transcription factors are secreted rapidly upon infection, thus priming immune response in neighboring cells [144]. Virus-driven secretomes can also impact cellular and tissue physiology, as demonstrated by two recent studies that examined how molecules secreted by herpesvirus infected cells determine local immune and growth responses in neutrophils [145] and cortical brain cells [54], respectively.…”
Section: Defining the Cellular Landscape Representative Of Immune Activationmentioning
confidence: 99%